Evaluation of maize and bean, in pure stand, and mixed cropping in alternated strips - Vieira, Simião Alano; Ben, José Renato; Gastal, Flavio Luiz da Cunha (Pesquisa Agropecuaria Brasileira, 2014)
The behavior of corn (Zea mays L.) and beans (Phaseolus vulgaris L.) in pure stand and intercropped in alternated strips and peasant farming situation were studied in relation to grain production, land use efficiency, gross income and gross profit. The best grain production in corn was achieved with pure stand and alternated strips. The potential production of grain beans as a monoculture was reduced in 32% to 50% when planted in association with corn. Economic studies of grain yield performance over all systems, with relative values for 1978, showed that the treatments in alternated strips were the most profitable and they also gave a better effective land use with the index of 157%.